2006
DOI: 10.1007/s00439-006-0244-8
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the DAT1 and DRD2 genes to serious and violent delinquency among adolescents and young adults

Abstract: As far as we know, this is the first national study that reports compelling evidence for the main effects of genetic variants on serious and violent delinquency among adolescents and young adults. This study investigated the association between the self-reported serious and violent delinquency and the TaqI polymorphism in the DRD2 gene and the 40-bp VNTR in the DAT1 gene. The study was based on a cohort of more than 2,500 adolescents and young adults in the National Longitudinal Study of Adolescent Health in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(171 citation statements)
references
References 62 publications
(55 reference statements)
9
156
0
6
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21][22][23] Of these, eight had adopted a prospective longitudinal study design, 12,14,15,18,19,[21][22][23] three were case-control studies 16,17,20 and one was a transversal study. Six studies related aggressive behavior to genic expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16][17][18][19][20][21][22][23] Of these, eight had adopted a prospective longitudinal study design, 12,14,15,18,19,[21][22][23] three were case-control studies 16,17,20 and one was a transversal study. Six studies related aggressive behavior to genic expression.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies related aggressive behavior to genic expression. [12][13][14][15][16][17] Two demonstrated the genic expression of the serotonin transporter, 13,14 one demonstrated the genic expression of the monoaminaoxidase (MAOA), 12 another study demonstrated the genic expression of the transporter and the receptor of dopamine, 15 and two studies presented the genic expression of the catechol-O-methyltransferase enzyme (COMT). 16,17 Four studies related aggressive behavior to maternal exposure to psychoactive substances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as this study is crosssectional we cannot exclude the possibility that individuals seeking treatment as children are different from those seeking treatment as adults. This might be suggested by findings of other phenotypes associated with DAT1, such as decreased delinquency and promiscuous behavior in teenagers with the 9/9 genotype of the 3 0 -UTR VNTR (Guo et al, 2007).…”
Section: Total (95% Ci)mentioning
confidence: 90%
“…The increase in D2 receptors translates to enhanced DA function, which will ultimately promote greater confidence in the recovering addict, enabling a better understanding of the written word of the twelve-step fellowship. This will lead to an anti-stress effect and as such reduce the chance for relapse especially in dysfunctional and co-dependent families [25,32,42,156,169,258,272,274,[275][276][277][278].…”
Section: Eleventh-prayer and Meditation To Contact Godmentioning
confidence: 99%